Consumo residencial de agua en el sistema de ciudades de Colombia - Vivas Pacheco, Harvy (Sociedad y Economía, 2005)
This paper estímales the main determinants of water consumption generated by the network of cities in Colombia. The model corresponds to the aggregate versión in the rent-consumption space of a Stone-Geary runction that allows estimation of the differences in valuation and intensity of the preferences for the use of the resource. Results show a strong relationship between municipal consumption of water and the scale of urban income. The rates of preferences for the resource were highly significant and they show a clearly differntiated pattern.